Diagnosis of Hepatoma Using Grey Scale and Doppler Ultrasound in Patient with Chronic Liver Disease - Aneel Kumar, Tauqeer Anjum, Shahzeb Mastoi, Farah Naz Magsi, Jia Dodani, Pir Abdul Ahad Aziz Qureshi (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the efficacy of the greyscale and Doppler ultrasound in the diagnosis of hepatoma in chronic liver disease patients. Study Design: Prospective study. Place and duration of study: Department of Radiology, Jinnah Postgraduate Medical Centre Karachi from 1st October 2021 to 30th June 2022. Methodology: One hundred and twenty patients who were diagnosed with chronic liver diseases and were suspected of hepatocellular carcinoma were included in this study. Ultrasonography was conducted under grey scale Doppler scanning in each patient after 6 hours of fasting at 3-6 megahertz with a curvilinear probe in supine as well as oblique position. Sensitivity, specificity as well as the predictive value of the image formed through the ultrasonography machine was assessed. Results: The age of the patients was 46.5±6.5 years and there were 78 (65%) males whereas 42 (35%) were females. On the grey scale Doppler scan, there was 53% of cases seen confirmed for the presence of hepatoma. The sensitivity and specificity were observed in 65% and 85% of the grey scale Doppler ultrasonography while the positive predictive value was 92% respectively. Conclusion: Greyscale Doppler scan is an efficient and reliable method for the detection of hepatoma and can be used in clinically confirmed cases of chronic liver disease as a screening tool. Keywords: Hepatoma, Greyscale, Doppler ultrasound, Chronic liver disease